Nalar Kritis Pemikiran Rasional-Sufistik Muhammad Abid Al-Jabiri dalam Ilmu Keagamaan - Ahmad Zayyadi; Nurlaela Nurlaela (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
This article examines the religious sciences in the thought of Mohammed Abid al-Jabiri which is well known, namely bayani, irfani, and burhani. Bayani is a source of knowledge from a text or reasoning from the text. Whereas irfani comes from science or methods of kasyf (dzauq) which are intuitive and sufistic. This epistemology is very difficult to rationalize, because one has to experience it for yourself if you want to know. Burhani holds that the source of knowledge is reason (ratio) or is called philosophical. The method used in this paper uses a philosophical approach starting from the epistemology of bayani in the form of text (nash), irfani in the form of direct experience, and epistemology of burhani based on reality (al-waqi), both natural, social and even religious realities (religious) in the perspective of Muhmmad thought Abid alJabiri. The thought contribution is expected to enlighten Islamic thought in facing the plurality of humanity both internally and externally, so that the correlation through this epistemological approach can be felt in the empirical world.